2005
DOI: 10.1074/jbc.c400587200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Retropseudogenes from Pluripotent Cell-specific Gene Expression Indicates a Potential Signature for Novel Gene Identification

Abstract: Oct4, Nanog, and Stella are transcription factors specifically expressed in embryonic stem (ES) cells and germ lineage cells that impart critical functions in the maintenance of pluripotency. Here, we report the excessive frequency and apparent selectivity of retrotransposition of ES cell-specific genes. Six highly homologous pseudogenes for Oct4, 10 for Nanog, and 16 for Stella were identified by nucleotide BLAST (basic local alignment sequence tool) searches against the respective gene mRNA transcripts. Of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
93
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 17 publications
0
93
0
Order By: Relevance
“…Yet, only about 10% of cellular genes have one or more retroposed copies in the genome [21,23]. While the effects of germline expression [23,25,26] and genomic stability [23,27,28] have been studied previously, little is known about the influence of RNA stability and translation on retroposition of PPs. …”
mentioning
confidence: 99%
“…Yet, only about 10% of cellular genes have one or more retroposed copies in the genome [21,23]. While the effects of germline expression [23,25,26] and genomic stability [23,27,28] have been studied previously, little is known about the influence of RNA stability and translation on retroposition of PPs. …”
mentioning
confidence: 99%
“…These cells included the marrowisolated adult multi-lineage inducible (MIAMI) cells, multipotent adult progenitor cells (MAPC), bone marrow derived germ cells, very small embryonic-like (VSEL) cells, and other subpopulations of MSCs defined by cell surface markers and the ability to grown in specific media formulations. [22][23][24][25] The use of RT-PCR to define Oct4 positive cells has recently been called into question by several groups describing Oct4 retropseudogenes that are actively transcribed in both normal and transformed cells [26][27][28] (and Liedtke et al). A number of these pseudogenes encompass nearly the entire Oct4 coding sequence and are actively transcribed, confounding the interpretation of RT-PCR results since both minor contamination of isolated RNA with genomic DNA and pseudogene expression can contribute to false positive signals if primers are not carefully designed.…”
mentioning
confidence: 99%
“…Furthermore, at least six pseudogenes are actively transcribed in hESC (17,25). Functional studies of OCT4 in hESC should therefore distinguish between the isoforms that are being evaluated (39).…”
Section: Discussionmentioning
confidence: 99%
“…An immunohistochemical study of OCT4 expression in early human embryos showed that OCT4A is expressed in the nuclei of the inner cell mass and trophectoderm, while OCT4B segregates to the trophectoderm cytoplasm (5), suggesting differential functions for OCT4A and OCT4B. To further complicate the regulation of OCT4 and interpretation of human OCT4 studies, there are six transcribed pseudogenes for OCT4, with up to 95% homology to the endogenous gene (17,25). Functional RNA interference studies in hESC demonstrated that OCT4 downregulation leads to trophectoderm and endoderm differentiation (13,20,32,45,46).…”
mentioning
confidence: 99%